4 civil engineering undergraduates create history in Taiwan - UMP, PNC
Four Faculty of Civil Engineering & Earth Resources diploma undergraduates of Universiti Malaysia Pahang (UMP) created history when they collected two gold medals, two silver medals and six Special Awards in the International Exhibition for Young Inventors (IEYI 2012).